2000
DOI: 10.1021/jp001133+
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Brewster Angle Microscopy Studies of Fatty Acid/Cholesterol Mixtures at the Air/Water Interface

Abstract: Mixtures of cholesterol with stearic (STA), oleic (OA), and linoleic (LA) acids spread as monolayers at the air/water interface were used as model systems to examine the hypocholesterolemic effect of fatty acids. Miscibility and interactions between the components of the cholesterol/fatty acid systems were studied basing on the analysis of surface pressure/area isotherms completed with Brewster angle microscopy images. In monolayers, STA and cholesterol were found to be immiscible. In contrast, OA and LA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
62
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 25 publications
(42 reference statements)
12
62
0
Order By: Relevance
“…The brightness of image (l) was also similar to that of x C = 0.2 ((h)); the homogeneous mixed monolayer was formed on the water surface. These images ((i)-(l)) are similar to the monolayer formation process of such as stearic acid [18] and the following Chol ((m)-(p) in Figure 3), which forms the condensed monolayer on the water surface. Therefore, at x C = 0.3, a condensed monolayer was formed on the water surface from the initial stage of the monolayer formation.…”
Section: Brewster Angle Microscopy (Bam)supporting
confidence: 55%
See 1 more Smart Citation
“…The brightness of image (l) was also similar to that of x C = 0.2 ((h)); the homogeneous mixed monolayer was formed on the water surface. These images ((i)-(l)) are similar to the monolayer formation process of such as stearic acid [18] and the following Chol ((m)-(p) in Figure 3), which forms the condensed monolayer on the water surface. Therefore, at x C = 0.3, a condensed monolayer was formed on the water surface from the initial stage of the monolayer formation.…”
Section: Brewster Angle Microscopy (Bam)supporting
confidence: 55%
“…On pure Chol monolayer, we obtained typical images that observed in the case of condensed monolayer [18]- [20]. At quite a low SP of 1 mN/m, the image showed lineand circle-type domain state ((m)), as well as x C = 0.3 ((I) in Figure 3).…”
Section: Brewster Angle Microscopy (Bam)mentioning
confidence: 78%
“…In our previous studies on polyether-based polymers with Ch moieties and systematically varied molecular architectures, it has been found that at this point the lPEG and hbPG blocks of ChP are located on the air-water interface (in addition to the Ch moiety) and contribute to the mmA value [54]. Thus, the Ch moiety is forced to be only in the G state and the LC domain formation typical for pure Ch in this region is prevented [60][61][62][63]. The Langmuir isotherms of the neat diblock copolymer in the relevant region are shown as gray curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The excess molar volume [13][14][15] . shows the variation of V exc cyclo with x cyclo and also that of V exc hexane with x hexane at 30, 40 and 50 o C. Open symbols denote cyclohexane/benzene system and closed ones, hexane/benzene system.…”
Section: Resultsmentioning
confidence: 99%